Dampak Social Media Marketing terhadap Minat Beli Melalui E-Word of Mouth pada Kosmetik Focallure - Latifah, Durohtul; Yun, Yun (Journal of Management and Bussines (JOMB), 2024)
The purpose of this research is to provide solutions to the research problems identified, so it is important to leverage the knowledge that purchasing interests can be influenced by several variables. Lower purchasing interest rates can be influenced by e-word from mouth, while e word from mouse can be predicted by social media marketing, which is better social media advertising, will produce better e- word and consumer buying interest in Focallure cosmetic Focallure. The instruments used in this study are pronounced to pass validity tests and reliability tests.The instrument used as a data collection tool respondents are Instagram followers Focallure in Bandung City who are interested and who have experience buying Focallura products that are the object of evaluation in this purchase of 90 people. The data collection technique used is cross-sectional or one-shot study. The data analysis techniques used are simple regression and double regression using SPSS version 26 assistive tools and using a single test. Of the four proposed hypotheses, the entire hypothesis is supported by empirical data. The findings show that e-word of mouth can mediate the influence of social media marketing on buying interests. Kata Kunci : Social Media Marketing, Minat Beli, E-Word Of Mouth